2015
DOI: 10.33073/pjm-2015-018
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antibacterial activity of essential oils of two species of Lamiaceae against phytopathogenic bacteria

Abstract: A b s t r a c tIn this study, we aimed to determine chemical composition and antibacterial activities of Satureja hortensis and Calamintha nepeta against to 20 phytopathogenic bacteria causing serious crop loss. The essential oils of S. hortensis and C. nepeta were isolated by the hydrodistillation method and the chemical composition of the essential oils were analyzed by GC-MS. The antibacterial properties of the essential oils were evaluated against 20 phytopathogenic bacteria through Disc diffusion assay an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 46 publications
4
25
1
Order By: Relevance
“…It was observed that the highest inhibitory effect against the used bacteria was obtained in highest concentration (500 μg/ml) and that inhibition effect was lower than these obtained with antibiotics. In the literature, it has been shown that the antimicrobial activity of plant compounds can be folded double than antibiotics (Gormez et al 2015). However, the results obtained in this study shows lower antibacterial effect than these antibiotics tested.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…It was observed that the highest inhibitory effect against the used bacteria was obtained in highest concentration (500 μg/ml) and that inhibition effect was lower than these obtained with antibiotics. In the literature, it has been shown that the antimicrobial activity of plant compounds can be folded double than antibiotics (Gormez et al 2015). However, the results obtained in this study shows lower antibacterial effect than these antibiotics tested.…”
Section: Resultscontrasting
confidence: 53%
“…All the experimental groups were incubated at 37 °C for 24 hours. At the end of the specified period, transparent inhibition zone diameters around the standard discs were measured and recorded (Gormez et al 2015).…”
Section: Testing the Effectiveness By Disk Diffusion Methodsmentioning
confidence: 99%
“…Therefore, search for novel alternative crop protectants is becoming more and more important. Recently, a wide range of essential oils (EOs) have been extensively studied for their antibacterial activity against many plant pathogenic bacteria (Deans & Ritchie, 1987;Vasinauskiene et al, 2006;Dadasoglu et al, 2011;Kokoskova et al, 2011;Hossein Nezhad et al, 2012;Badawy & Abdelgaleil, 2014;Gormez et al, 2013Gormez et al, , 2015Gakuubi et al, 2016;Todorović et al, 2016;Popović et al, 2017), usually using a direct-contact antimicrobial assay (Bajpai et al, 2011). Essential oils as products of plant secondary metabolism are the most interesting substances possessing antimicrobial activity (Deans & Ritchie, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…This growing interest in finding bio-pesticides in order to control the diseases is emphasized by the fact that the diseases caused by the plant pathogenic bacteria of Xanthomonas species are still a major problem even in the developed countries (McManus et al, 2002). Recently, a wide range of essential oils (EOs) have been extensively studied for their activity against many phytopathogenic bacteria (Gormez et al, 2015;Gakuubi et al, 2016;Todorović et al, 2016;Popović et al, 2017), usually using a direct-contact antimicrobial assay (Bajpai et al, 2011). Polyphenol oxidases (PPOs) are a group of Cu-containing enzymes that catalyse the oxidation of several phenols to o-quinones (Oliveira et al, 2011;van Gelder et al, 1997).…”
Section: Introductionmentioning
confidence: 99%